Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3390/ijerph14101169
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Resistant Klebsiella pneumoniae Isolated from Austrian River Water

Abstract: Antibiotic-resistant bacteria are spreading worldwide in medical settings but also in the environment. These resistant bacteria illustrate a major health problem in our times, and last-line antibiotics such as tigecycline represent an ultimate therapy option. Reports on tigecycline non-susceptible Enterobacteriaceae are presented with regard to medical settings but are rare with that for the environment. The aim of this study was to characterize two tigecycline non-susceptible Klebsiella pneumoniae isolates fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…However, Nielsen et al (2014) reported that the IS5 insertion element increased the MIC of tigecycline by four-fold and was not dependent on the functional AcrAB-TolC efflux pump, suggesting that the AcrAB-TolC efflux pump is not the only mechanism causing tigecycline resistance. Hladicz et al (2017) reported that RamR is a repressor that prevents the overexpression of ramA; when ramR is mutated, ramA is overexpressed, leading to tigecycline resistance; this mechanism was confirmed by Li et al (2017). However, in the current study, no mutation in ramR was detected.…”
Section: Discussionsupporting
confidence: 52%
“…However, Nielsen et al (2014) reported that the IS5 insertion element increased the MIC of tigecycline by four-fold and was not dependent on the functional AcrAB-TolC efflux pump, suggesting that the AcrAB-TolC efflux pump is not the only mechanism causing tigecycline resistance. Hladicz et al (2017) reported that RamR is a repressor that prevents the overexpression of ramA; when ramR is mutated, ramA is overexpressed, leading to tigecycline resistance; this mechanism was confirmed by Li et al (2017). However, in the current study, no mutation in ramR was detected.…”
Section: Discussionsupporting
confidence: 52%
“…As a new class of environmental contaminants, antibiotics have been the subject of numerous discussions due to their large-scale usage and long-term adverse effects [ 1 , 2 , 3 ]. Thousands of tons of antibiotics are used for therapeutic purpose or as animal growth promoters every year [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…16,19 The transcription of ramA, marA, and soxS is repressed by RamR, MarR, and SoxR, respectively. 13,26 RamA is also regulated by Lon protease. 27,28 As RamR directly represses the expression of ramA, loss-of-function mutations in ramR can cause the overexpression of ramA.…”
mentioning
confidence: 99%